Refining Traditional and Modern: A Literary Study of Indonesian Sufism and Neo-Sufism from Pesantren - Wahyuni, Yuyun Sri (DINIKA : Academic Journal of Islamic Studies, 2017)
Scholars have predicted that Sufism and other forms of traditional Islamic practices would disappear as modernity comes into society. Considering this view on religion and the modern, based on the literary study, this paper examines the historical development of Islam, Sufism, and pesantren in Indonesia, or previously known as Nusantara. Sufi preachers, known as walisongo, brought Islam to Indonesia and in a very short of time brought most of Indonesians into voluntary conversions. After walisongo, Indonesian ulama carried the dakwah Islamiyah through different Sufi networks and pesantrens. In the modern era, Sufism and other means of traditional practices face the challenges of disappearance and then transform themselves into neo-Sufism. The discussions in this paper show how Sufism, through its various ways, mingle with the different era in Indonesia and reshape the meaning of traditional and modern in Indonesia.Â Keywords:Islam Indonesia, Sufism, and pesantren,